SISTEM PENGATURAN LAMPU LALU LINTAS SECARA SENTRAL DARI JARAK JAUH - May On, Tjia; Mardjoko, Pono Budi; Martanto, Nato (TESLA Jurnal Teknik Elektro UNTAR, 2007)
Scheme of traffic light system arrangement in central from long distance to help Dinas Perhubungan (Dishub) in arranging the traffic the traffic light according to the traffic situation.